Effectiveness of using noncontingent escape for general behavior management in a pediatric dental clinic. Issue 4 (30th September 2013) - Allen, Keith D.; Wallace, Dustin P.
<x xml:space="preserve">Abstract</x> In a randomized controlled trial, 151 children 2 to 9 years old were exposed to either usual behavior management or to a fixed‐time schedule of brief breaks (noncontingent escape) from ongoing dental treatment. Results demonstrated that the routine delivery of scheduled breaks from treatment significantly reduced the vocal and physical disruptive behavior and the need for restraint in a nonclinical sample of children undergoing restorative dental treatment. In addition, the treatment did not add significantly to the typical time spent on behavior management by dentists. Together with findings from previous studies, these results suggest that using brief breaks from ongoing dental treatment has good efficacy, acceptability, and generality and may be a useful management tool, both in everyday dental practice and in more demanding instances of specialized need.